The Relevansi Pengetahuan Masyarakat dengan Sains Ilmiah pada Rumah Adat Desa Beleq Sembalun Lawang - Muizzatissalmi, Hadyatul; Arafani, Wahyuni; Darma Putra, Kadek Sukma; Al Idrus, Agil; Hadiprayitno, Gito; Andayani, Yayuk (Contextual Natural Science Education Journal, 2024)
The role of local wisdom in building cultural and national identity has veryimportant relevance in a society. By studying ethnoscience, we canunderstand different cultural ways of thinking and perspectives in explainingscientific phenomena. One of the local wisdoms in West Nusa Tenggara isthe traditional house of Beleq Village. This traditional house has a roofmade of reeds and poles and walls made of bamboo. The use of naturalmaterials as building materials by the Sembalun community has its ownphilosophy and reasons. The aim of this research is to obtain more detailedinformation regarding the relevance of public knowledge and scientificknowledge regarding the use of reeds and bamboo as building materials fortraditional houses in Beleq Village. The method used is a qualitativemethod. The results of this research show that use of reeds as a roof is abletoreverse the temperature. This is in line with sacientific knowledgeregarding the ability of alang-alang as an insulator in the thermal insulationprocess. Apart from that, the use of bamboo as poles, walls and roof trussesfor traditional houses has the ability to provide the strongest support and atthat time bamboo was easy to find. This is in line with scientific knowledgeregarding bamboo's ability to be a sustainable plant and become stronger ifdried. So, it can be concluded that there is relevance between publicknowledge an scientific science.